Analysis of the leadership profile of soccer coaches of Brazilian youth teams - Costa, Israel Teoldo da; Samulski, Dietmar Martin; Costa, Varley Teoldo da (Brazilian journal of physical education and sport, 2009)
This study aimed to identify the factors derived from the real leadership style of soccer coaches. This study used a questionnaire to characterize the sample and the Revised Leadership Scale for Sport, real profile version, as instruments for data collection. One hundred and nine soccer coaches of youth teams participated of this research. They presented an average age of 38.64 years (± 10.33) and a direct involvement with coaching of 7.05 years (± 6.01). The interviewees were coaches of four age groups: under 20's (33 coaches), under 17's (28 coaches), under 15's (25 coaches) and under 13's (23 coaches). The results showed that the coaches interviewed perceive themselves as autocratic and orientated to training-instruction aspects as the main components of their leadership profile. The study also found that there were no statistical differences between coaches of the four age groups studied. Therefore, it is possible to conclude that, the real profile of leadership for soccer coaches in youth teams combines autocratic decision style and the technical, tactical and motivational performance of the team; and that the interviewed coaches have the same leadership profile independently of the age group they work with.